Chronicle of Academic Activities in the Field of Economic History in Poland (April 1977 - May 1978) - Górczyńska, Bożena (Studia Historiae Oeconomicae, 1979)
Abstrakt w języku oryginalnym This chronicle presents a detailed account of academic activities in the field of economic history in Poland between April 1977 and May 1978. It documents a series of national and international conferences, symposia, and scholarly sessions that reflect the evolving focus and methodological concerns of Polish economic historians during this period. The primary aim of the document is to summarize and contextualize the intellectual trends, research themes, and institutional collaborations that shaped economic history scholarship in Poland in the late 1970s. These activities included sessions on forced labor under the Third Reich, theoretical-methodological approaches to economic history, regional monograph studies, the political and social structure of Polish society, and the wartime economies of Axis powers. The chronicle is based on reports from academic institutions, universities, and research commissions, and highlights contributions from both Polish and international scholars. Particularly noteworthy is the international symposium held in Jaszowiec in February 1978, which examined the wartime economies of Axis countries with a focus on the role of occupied and dependent states. This chronicle not only captures the scope and diversity of economic historical research in Poland at the time, but also contributes to mapping the international scholarly dialogue in preparation for major conferences such as the 1978 International Congress of Economic History in Edinburgh.